Splenic Abscess after Sleeve Gastrectomy - Rany Aoun; Michel Gabriel; Elias El Haddad; Roger Noun; Ghassan Chakhtoura (Case Reports in Medicine)
Splenic abscess is a very rare complication of laparoscopic sleeve gastrectomy (LSG). Clinical presentation includes fever, leucocystosis, and abdominal pain. CT SCAN is a must for diagnosis. The preferred treatment is either conservative, with intravenous antibiotics and percutaneous drainage, or splenectomy. We report the thirteen case of a splenic abscess after LSG. In our patient, the abscess occurred three weeks after LSG in a 21-year-old man, and it was successfully treated conservatively.